The Role of Qur'anic Dialogues in Surah Yusuf and Their Use to Develop Speaking Skills - Irvan, Muhammad; Kholik Hasan, Moch. Abdul; Abd Faishol (Ukazh: Journal of Arabic Studies, 2025)
This study aims to identify the role of Qur'anic dialogues in Surah Yusuf and use them to develop speaking skills. The researcher used a descriptive-analytical approach, by seeking information related to the topic to achieve results, analyzing those results and then applying them to develop proficiency in speaking. The dialogues contained in Surah Yusuf include sixteen dialogues. The dialogues include the dialogue after Joseph had a dream consisting of 5 verses, the dialogue of the beginning of Joseph in the trade consisting of 3 verses, the dialogue about Joseph's murder plan consisting of 5 verses, the dialogue after executing Joseph consisting of 3 verses, the dialogue of adultery accusations against Joseph consisting of 1 verse, the defense dialogue from Joseph against adultery accusations consisting of 4 verses, the dialogue about Joseph's innocence decision consisting of 6 verses, the dialogue of the beginning of yusuf in prison consisting of 7 verses, the dialogue of 7 verses, the dialogue about the king's dream consisting of 7 verses, the dialogue about the initial signs of the conspiracy consisting of 3 verses, the dialogue about the rewards given to yusuf after explaining the king's dream consisting of 4 verses, the dialogue about bringing Benjamin to the city of Egypt consisting of 5 verses, the dialogue about considering the reasons for bringing Benjamin to the city of Egypt consisting of 4 verses, the dialogue about the accusation of theft against Benjamin consisting of 10 verses, the dialogue about bringing Benjamin to the city of Egypt consisting of 5 verses.